2020
DOI: 10.3390/catal10060634
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Benzodiazepines Synthesis

Abstract: This review is focused on palladium-catalyzed reactions as efficient strategies aimed at the synthesis of different classes of benzodiazepines. Several reaction typologies are reported including hydroamination, amination, C–H arylation, N-arylation, and the Buchwald–Hartwig reaction, depending on the different substrates identified as halogenated starting materials (activated substrates) or unactivated unsaturated systems, which then exploit Pd(0)- or Pd(II)-catalytic species. In particular, the use of the dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…The method allows the formation of indoline and oxindole derivatives as well as polyheterocyclic molecules [2a] . A wide range of approaches are available in the synthesis of benzodiazepines including hydroamination, amination, C−H arylation, N ‐arylation, and the Buchwald–Hartwig reaction induced either by Pd 0 or Pd II catalysts [2b] …”
Section: Introductionmentioning
confidence: 99%
“…The method allows the formation of indoline and oxindole derivatives as well as polyheterocyclic molecules [2a] . A wide range of approaches are available in the synthesis of benzodiazepines including hydroamination, amination, C−H arylation, N ‐arylation, and the Buchwald–Hartwig reaction induced either by Pd 0 or Pd II catalysts [2b] …”
Section: Introductionmentioning
confidence: 99%
“…Although already described in 1929 by Le Fèvre, [11] only limited reports for the construction of 1,3‐diazepines are known. Despite considerable recent synthetic efforts in this area, [1d,3a,b,d,12–26] the synthesis of functionalized 1,3‐diazepine derivatives remains a challenging task. Therefore, better synthetic routes to the 1,3‐diazepine framework from readily available starting materials are desirable.…”
Section: Introductionmentioning
confidence: 99%
“…[ 36 ] Another review was reported on the synthesis of benzodiazepines through palladium catalysis. [ 37 ]…”
Section: Introductionmentioning
confidence: 99%